2005
DOI: 10.1002/hc.20084
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective synthesis, structure and behavior in solutions of novel phosphorylated thiazolidin‐4‐ones

Abstract: Regioselective syntheses of novel 2-(phosphoryl)methylidenethiazolidine-4-ones

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The cyclization of phosphonyl-containing compounds 223 with acetylenedicarboxylic ester [113] proved to be a convenient regiospecific method for the synthesis of phosphorylated thiazolidin-4-ones 224A, the structure of which was confirmed by X-ray crystallographic analysis. In solution the latter undergo polymerization to Z,Z-thiazolidin-4-ones 224B probably through the imine configuration.…”
Section: Heterocyclizations Of Phosphonylthioacetamidesmentioning
confidence: 89%
See 1 more Smart Citation
“…The cyclization of phosphonyl-containing compounds 223 with acetylenedicarboxylic ester [113] proved to be a convenient regiospecific method for the synthesis of phosphorylated thiazolidin-4-ones 224A, the structure of which was confirmed by X-ray crystallographic analysis. In solution the latter undergo polymerization to Z,Z-thiazolidin-4-ones 224B probably through the imine configuration.…”
Section: Heterocyclizations Of Phosphonylthioacetamidesmentioning
confidence: 89%
“…At the same time, however, the phosphoruscontaining compounds exhibit certain types of biological activity [109][110][111]. The recently developed new preparative method for the synthesis of 2-phosphonylthioacetamides [112] has therefore prompted development of the chemistry of these compounds [113,114].…”
Section: Heterocyclizations Of Phosphonylthioacetamidesmentioning
confidence: 99%
“…41 Analysis of the 31 P and 1 H NMR spectra showed that the shift of the E,Z 12-Z,Z 12 equilibrium is governed by the solvent polarity. For instance, in nonpolar sol vents, such as C 6 D 6 , the equilibrium is shifted toward the E,Z isomer.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown recently [9] that the reaction of dimethyl acetylenedicarboxylate (DMAD) with thioamides (1) is a convenient method for the synthesis of phosphorylated thiazolidin-4-ones (2) with an E,Z-structure. The reactions of DMAD with thioamides 3 containing polyfluoroalkyl substituents [11,24] differ from the cycloacylation of the unfluorinated substrates.…”
Section: Reactions With Acetylenedicarboxylic Estermentioning
confidence: 99%
“…Therefore, in spite of the fact that the first papers on this subject were published 50 of more years ago [7,8] synthetic investigations in the field are continuing to this day [9][10][11][12].…”
mentioning
confidence: 92%